The ELECTRONIC AUDIO READING AID LECTURE (E-ARAL): INTERVENTION IN DEVELOPING READING COMPREHENSION AND ANALYSIS OF TEXTS - DAYAG, FELY (International Journal of Business, Law, and Education, 2022)
This study determined the effectiveness of the Electronic Audio Reading Aid Lecture (E-ARAL) in the subject Reading and Analysis of Various Texts towards Research. This study addressed the Republic Act 10533 which encourages the development and reproduction of instructional materials. This study used a pre-test-post-test design. The respondents are chosen purposively with a grade of 79 and below and divided into two groups the control and experimental group. The control group used the traditional method and the experimental group used the intervention E-ARAL in teaching the lesson. The mean score of the pre-test and post-test of the two groups are both analyzed to determine their significant differences. In conclusion, the utilization of traditional teaching and the intervention E-ARAL are both effective in teaching the subject, but the intervention E-ARAL is more effective because of the higher mastery level results. Lastly, there was a significant difference between the experimental and control groups.